Optical coherence tomography versus angiography and intravascular ultrasound to guide coronary stent implantation: A systematic review and meta‐analysis. (17th October 2022) - Siddiqi, Tariq Jamal; Khan, Muhammad Shahzeb; Karimi Galougahi, Keyvan; Shlofmitz, Evan; Moses, Jeffrey W.; Rao, Sunil; West, Nick E. J.; Wolff, Eric; Hochler, Jason; Chau, Karen; Khalique, Omar; Shlofmitz, Richard A.; et al.
Abstract: Background: Optical coherence tomography (OCT) is an adjunct to angiography‐guided coronary stent placement. However, in the absence of dedicated, appropriately powered randomized controlled trials, the impact of OCT on clinical outcomes is unclear. Objective: To conduct a systematic review and meta‐analysis of all available studies comparing OCT‐guided versus angiography‐guided and intravascular ultrasound (IVUS)‐guided coronary stent implantation. Methods: MEDLINE and Cochrane Central were queried from their inception through July 2022 for all studies that sought to compare OCT‐guided percutaneous coronary intervention (PCI) to angiography‐guided and IVUS‐guided PCI. The primary endpoint was minimal stent area (MSA) compared between modalities. Clinical endpoints of interest were all‐cause and cardiovascular mortality, major adverse cardiovascular events (MACE), myocardial infarction (MI), target lesion revascularization (TLR), target vessel revascularization (TVR), and stent thrombosis (ST). Risk ratios (RRs) and mean differences (MDs) with their corresponding 95% confidence intervals (CIs) were pooled using a random‐effects model. Results: Thirteen studies (8 randomized control trials and 5 observational studies) enrolling 6312 participants were included. OCT was associated with a strong trend toward increased MSA compared to angiography (MD = 0.36, p = 0.06). OCT‐guided PCI was also associated with a reduction in the incidence of all‐cause mortality [RR = 0.59, 95% CI (0.35, 0.97), p = 0.04] and cardiovascular mortality [RR = 0.41, 95% CI (0.21, 0.80), p = 0.009] compared with angiography‐guided PCI. Point estimates favored OCT relative to angiography in MACE [RR = 0.75, 95% CI (0.47, 1.20), p = 0.22] and MI [RR = 0.75, 95% CI (0.53, 1.07), p = 0.12]. No differences were detected in ST [RR = 0.71, 95% CI (0.21, 2.44), p = 0.58], TLR [RR = 0.71, 95% CI (0.17, 3.05), p = 0.65], or TVR rates [RR = 0.89, 95% CI (0.46, 1.73), p = 0.73]. Compared with IVUS guidance, OCT guidance was associated with a nonsignificant reduction in the MSA (MD = −0.16, p = 0.27). The rates of all‐cause and cardiovascular mortality, MACE, MI, TLR, TVR, or ST were similar between OCT‐guided and IVUS‐guided PCI. Conclusions: OCT‐guided PCI was associated with reduced all‐cause and cardiovascular mortality compared to angiography‐guided PCI. These results should be considered hypothesis generating as the mechanisms for the improved outcomes were unclear as no differences were detected in the rates of TLR, TVR, or ST. OCT‐ and IVUS‐guided PCI resulted in similar post‐PCI outcomes.